Reduced latency in restricted flooding routing protocol for mobile ad hoc network. - A. Latif, Liza; Ali, A.; Fisal, Norsheila (2007)
Packet delivery and latency are several performance metrics used to determine the effectiveness of a new routing algorithm. The multiple access protocol in Mobile Ad Hoc Network (MANET) requires nodes to contend for the shared medium when transmitting route request (RREQ) in the route discovery phase and this will create a broadcast storm which increases the probability of packet collisions despite utilizing the normal access technique for wireless networks. With location information of the destination node, the source node and also of the current node, RREQ will be more directed towards destination since nodes that are within the directed region will participate in the routing process. This paper presents Quadrant-based directional routing protocol (Q-DIR) algorithm that restrict the broadcast region to a quadrant where the destination node and source node are located. With Q-DIR as a pure reactive routing protocol which is a modified AODVbis, latency of packets will be further reduced and consequently, increases the delivery ratio. This paper will present the performance of Q-DIR in a network of 49 nodes of which the nodes are static.